(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2020)
In order to contrast the CoViD-19 pandemic emergency, the Italian Government imposed several restrictions on fundamental liberties, and in some cases even suspended them. Although many administrative tribunals eventually confirmed the legitimacy of those measures, this article discusses it from the point of view of constitutional law, especially on the basis of the proportionality test.